Measurements of fractional exhaled nitric oxide in pediatric asthma - Youn-Soo Hahn (Korean Pediatric Society, 2013)
Exhaled nitric oxide (NO) has been extensively investigated as a noninvasive marker of airway inflammation in asthma. The increased NO expression induced by inflammatory mediators in airways can be monitored easily in exhaled air from asthmatic children. Based on the relationship between the increased NO expression and eosinophilic airway inflammation, fractional exhaled nitric oxide (FeNO) measurements become an important adjunct for the evaluation of asthma. In addition, the availability of portable devices makes it possible to measure FeNO more easily and frequently in the routine pediatric practice. Despite various confounding factors affecting its levels, FeNO can be applicable in diagnosing asthma, monitoring treatment response, evaluating asthma control, and predicting asthma exacerbations. Thus, although pulmonary function tests are the standard tools for objective measurements of asthmatic control, FeNO can broaden the way of asthma monitoring and supplement standard clinical asthma care guidelines.